Combined extradural and intradural approach to a trigeminal nerve hemangiopericytoma with cranial nerve monitoring: a technical note of a rare case. Issue 10 (23rd October 2022) - Frantzias, Joseph; Ghimire, Prajwal; Lavrador, Jose P; Pereira, Noemia; Bhangoo, Ranjeev; Thomas, Nicholas
Abstract: Hemangiopericytoma (HPC) of the trigeminal nerve is extremely rare. We present a case of a large cystic HPC of the mandibular division of the trigeminal nerve, only the third case described in the literature, with both intradural and extradural components. We describe the surgical approach, assisted by neurophysiological techniques of mapping and monitoring including blink reflex and triggered electromyography. Additionally, we report a method of monitoring of the sensory branches of the trigeminal nerve, poorly described in the literature, through peripheral and direct nerve stimulation and recording of transcranial somatosensory evoked potentials.